2021
DOI: 10.1111/ijd.15539
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil as adjunctive therapy to corticosteroids for the treatment of pyoderma gangrenosum: a case series and literature review

Abstract: Pyoderma gangrenosum is a rare neutrophilic dermatosis that is commonly treated with systemic corticosteroids; however, their potent side effects may warrant tapering, and non‐steroidal systemic immunosuppressants may help maintain or bolster disease clearance during weaning. Although cyclosporine is regarded as a favorable corticosteroid‐sparing agent, it is associated with several side effects, such as renal toxicity and hypertension, that may limit its feasibility. Mycophenolate mofetil is a well‐tolerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Biologic therapy with TNF‐a inhibitors can be a useful addition; however, patients may decline biologics due to side effect profile such as in this case 13 . Alternatively, studies have shown support for the use of mycophenolate mofetil and oral dapsone such as in this patient 13–15 . Topical tacrolimus has also been shown to enhance epithelialization of PG lesions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Biologic therapy with TNF‐a inhibitors can be a useful addition; however, patients may decline biologics due to side effect profile such as in this case 13 . Alternatively, studies have shown support for the use of mycophenolate mofetil and oral dapsone such as in this patient 13–15 . Topical tacrolimus has also been shown to enhance epithelialization of PG lesions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Another literature review reported the results of multiple case series totaling 63 patients treated with MMF. The result shows that 93% of patients improved on MMF, with five patients achieving complete remission [ 10 ]. Surprisingly, our patient had several moderate-to-severe relapses when prednisone was tapered.…”
Section: Discussionmentioning
confidence: 99%
“…Pyoderma gangrenosum is a neutrophilic dermatosis that is characterised by non-infective necrotic ulceration of the skin. 50,51 It is a rare condition with an annual incidence of 3-10 per million. 50 It is associated with a unilateral PUK that responds well to systemic CS and immunosuppression agents.…”
Section: Dermatosismentioning
confidence: 99%
“…50,51 It is a rare condition with an annual incidence of 3-10 per million. 50 It is associated with a unilateral PUK that responds well to systemic CS and immunosuppression agents. 50,51,52,53,54 Erythema elevatum diutinum (EED) is a rare chronic dermatosis that is characterised by brown to purple plaques of the extensor surfaces of the skin.…”
Section: Dermatosismentioning
confidence: 99%